Increase on Strengths of Hot Weather Concrete by Self-Curing of Wet Porous Aggregate - Sampebulu’, V. (Institute of Research and Community Outreach - Petra Christian University, 2012)
The compressive and tensile strengths of concrete made in hot weather condition decreased due to loss of mixing water caused by high evaporation. One method to overcome the problem is the use of saturated fly ash aggregate. The water content in fly ash aggregate can flow out to the hardened cement paste to continue the hydration process. This “self-curing” mechanism could produce more hydration around the surface of fly ash aggregate which sub¬sequently increases concrete strength. Experimental study has been conducted in temperature of 20o to 40o with humidity of 70% for dry curing, water curing, and nearly 100% for fog curing. Effect of self-curing could be justified as the strengths of concrete using fly ash aggregates is higher than concrete using fly ash aggregates covered with silane agent, and crushed stone aggregates. Even in high temperature, the self-curing could increase the strengths of concrete due to bond strength around the surface of each fly ash aggregates.